2009
DOI: 10.1002/pi.2626
|View full text |Cite
|
Sign up to set email alerts
|

Free radical copolymerization of N,N‐dimethylaminoethyl methacrylate with styrene and methyl methacrylate: monomer reactivity ratios and glass transition temperatures

Abstract: BACKGROUND: The properties of copolymers depend strongly on their composition; therefore in order to tailor some for specific applications, it is necessary to control their synthesis, and, in particular, to know the reactivity ratios of their constituent monomers. Free radical copolymerizations of N,N‐dimethylaminoethyl methacrylate (DMAEM) with styrene (ST) and methyl methacrylate (MMA) in toluene solution using 1‐di(tert‐butylperoxy)‐3,3,5‐trimethylcyclohexane as initiator at 70 °C were investigated. Monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This suggested that there was a greater contribution to the T g from MMA in the resultant copolymer (cf., BMA). Which was supported by previous reports of the dependence of the T g values of MMA copolymers, on the proportion of MMA [ 23 , 24 , 25 , 26 , 27 ]. In contrast, when the mol% fraction of VP was lowered to ~30%, and the proportion of MMA increased commensurately in PVBM 30/50/20 (cf., PVBM 40/50/10), an increase in the T g value of ~5 °C was observed.…”
Section: Resultssupporting
confidence: 89%
“…This suggested that there was a greater contribution to the T g from MMA in the resultant copolymer (cf., BMA). Which was supported by previous reports of the dependence of the T g values of MMA copolymers, on the proportion of MMA [ 23 , 24 , 25 , 26 , 27 ]. In contrast, when the mol% fraction of VP was lowered to ~30%, and the proportion of MMA increased commensurately in PVBM 30/50/20 (cf., PVBM 40/50/10), an increase in the T g value of ~5 °C was observed.…”
Section: Resultssupporting
confidence: 89%
“…The F–R equation represents one of the earliest attempts to linearize the copolymer composition equation : G=rSt HrFSt . …”
Section: Resultsmentioning
confidence: 99%
“…The K–T method introduces new parameters into the linearized copolymerization equation : η=true(rSt +rFSt αtrue)ξrFSt α, where η and ξ are functions of the parameters G and H , η=Gα+Hξ=Hα+H and α is a constant equals ( H max H min ) 1 / 2 where H max , H min are the highest and lowest values of H , respectively. The domain for the variation of ξ is between 0 and 1, whereas the domain for H is 0 and ∞.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the late 1980's, several studies have been published regarding the use of multifunctional initiators in different polymerization processes, including characterization and applications of the obtained polymer materials and the mathematical modeling of the reaction system, although the vast majority of these studies has been focused on the PS production . Since the beginning of the 21 st century, experimental and modeling studies related to the use of multifunctional initiators (bi, tri, and tetrafunctional molecules) in polymerization processes have been extended to other styrene, methyl methacrylate (MMA), vinyl chloride, vinyl acetate, and styrene/MMA copolymerization systems . Despite that, it seems correct to say that the commercial use of multifunctional initiators in free radicals polymerization reactions is related primarily to styrene bulk polymerization reactions.…”
Section: Introductionmentioning
confidence: 99%